A systematic approach to testing UML designs - Dinh-Trong, Trung T., author; France, Robert B., advisor; Ghosh, Sudipto, advisor; Bieman, James M., committee member; Malaiya, Yashwant K., committee member; Fan, Chuen-mei, committee member (Colorado State University. Libraries, 2006)
In Model Driven Engineering (MDE) approaches, developers create and refine design models from which substantial portions of implementations are generated. During refinement, undetected faults in abstract model can traverse into the refined model, and eventually into code. Hence, finding and removing faults in design models is essential for MDE approaches to succeed. This dissertation describes approach to finding faults in design models created using the Unified Modeling Language (UML). Executable forms of UML design models are exercised using generated test inputs that provide coverage with respect to UML-based coverage criteria. The UML designs that are tested consist of class diagrams, sequence diagrams and activity diagrams. The contribution of the dissertation includes (1) a test input generation technique, (2) an approach to execute design models describing sequential behavior with test inputs in order to detect faults, and (3) a set of pilot studies that are carried out to explore the fault detection capability of our testing approach. The test input generation technique involves analyzing design models under test to produce test inputs that satisfy UML sequence diagram coverage criteria. We defined a directed graph structure, named Variable Assignment Graph (VAG), to generate test inputs. The VAG combines information from class and sequence diagrams. Paths are selected from the VAG and constraints are identified to traverse the paths. The constraints are then solved with a constraint solver. The model execution technique involves transforming each design under test into an executable from, which is exercised with the general inputs. Failures are reported if the observed behavior differs from the expected behavior. We proposed an action language, named Java-like Action Language (JAL), that supports the UML action semantics. We developed a prototype tool, named UMLAnT, that performs test execution and animation of design models. We performed pilot studies to evaluate the fault detection effectiveness of our approach. Mutation faults and commonly occurring faults in UML models created by students in our software engineering courses were seeded in three design models. Ninety percent of the seeded faults were detected using our approach.
Department Head: L. Darrell Whitley.